Flexible and Transparent Graphene Electrode Architecture with Selective Defect Decoration for Organic Light‐Emitting Diodes. (8th January 2018) - Park, Ick‐Joon; Kim, Tae In; Yoon, Taeshik; Kang, Sumin; Cho, Hyunsu; Cho, Nam Sung; Lee, Jeong‐Ik; Kim, Taek‐Soo; Choi, Sung‐Yool
Abstract: Graphene produced by chemical vapor deposition (CVD) has attracted great interest as a transparent conducting material, due to its extraordinary characteristics such as flexibility, optical transparency, and high conductivity, especially in next‐generation displays. Graphene‐based novel electrodes have the potential to satisfy the important factors for high‐performance flexible organic light‐emitting diodes (OLEDs) in terms of sheet resistance, transmittance, work function, and surface roughness. In this study, flexible and transparent graphene electrode architecture is proposed by adopting a selective defect healing technique for CVD‐grown graphene, which results in several benefits that produce high‐performance devices with excellent stabilities. The proposed architecture, which has a multi‐layer graphene structure treated by a layer‐by‐layer healing process, exhibits significant improvement in sheet resistance with high optical transparency. For improving the charge transport property and mechanical robustness, various defect sites of the CVD‐grown graphene are successfully decorated with gold nanoparticles through a simple electroplating (EP) method. Further, a graphene‐based OLED device that integrates the proposed electrode architecture on flexible substrates is demonstrated. Therefore, this architecture provides a new strategy to fabricate graphene electrode in OLEDs, extending graphene's immense potential as an advanced conductor toward high‐performance, flexible, and transparent displays. Abstract : Flexible and transparent graphene electrode architecture with layer‐by‐layer defect healing is proposed for the high‐performance graphene‐based flexible organic light‐emitting diodes. Improved performance including excellent charge transport and mechanical robustness of the proposed electrode architecture is systemically investigated, showing synergetic effects of selective defect healing and structural advantages. The new graphene electrode architecture demonstrates the great possibilities for flexible and transparent graphene‐based displays.